Pelaksanaan Promosi Jabatan Berdasarkan Merit System Di Kabupaten Kolaka Dan Kendari Provinsi Sulawesi Tenggara: Implementation of Promotion Based on Merit System in Kolaka and Kendari, Southeast Sulawesi. - sabaruddin; Puji Prio Utomo; Taslim Fait (Universitas Warmadewa, 2021)
This study aims to determine the implementation of promotion based on merit system in Kolaka and Kendari, Southeast Sulawesi. In this study, researchers applied a qualitative approach with a case study method. The employed data collection techniques were in-depth interviews and documentation. The informants in this study were 15 people selected using a purposive sampling technique. After the data were collected, they were then analyzed using an interactive model. The results showed that job promotions in the selection for the Primary High Leadership Position (Indonesian: Jabatan Pimpinan Tinggi Pratama (JPTP)) was still considered problematic in the stages of selection, including in the application, assessment, and appointment stages. At the application stage, the number of employees registering to be candidates was very low since many employees considered that the selection was conducted only to meet the procedural requirements because the official who would take up the position had already been chosen earlier. Furthermore, at the assessment and appointment stages, the selection committees were considered less objective and not transparent in scoring and determining the top 3 candidates for each position. In addition, the announcement of those top 3 (three) was only based on the alphabet of the name without any recapitulation of the score gained by each candidate.